HUBUNGAN PERSONAL HYGIENE DAN PENGGUNAAN ALAT PELINDUNG DIRI DENGAN KEJADIAN DERMATITIS KONTAK - Adhinda Putri Pratiwi (LPPMK STIKES Widyagama Husada, 2023)
Dermatitis is a skin disorder that usually causes itching and is characterized objectively by patches, rashes or inflammation. Symptoms that are often felt include redness of the skin that occurs due to loading on the blood vessels, can cause swelling/bruising due to fluid buildup in the tissue, thickening of the skin and scratching. The factors that cause contact dermatitis are generally divided into two groups, namely direct and indirect factors. Direct factors include solubility properties, substances, formulas (solid, gas, and liquid), concentration factors and contact time, while indirect factors include age, gender, personal hygiene, race, temperature, humidity and use of Personal Protective Equipment (PPE). This study aims to determine the relationship between personal hygiene and the use of Personal Protective Equipment (PPE) with the incidence of contact dermatitis. The type of research used is cross sectional using a descriptive approach. Based on the results of the analysis test that has been carried out using the chi-square test, the results show that there is a relationship between personal hygiene (0.022) and the use of PPE (0.014) with the incidence of contact dermatitis. It is recommended that workers are expected to increase awareness in preventing occupational diseases, one of which is by paying more attention to personal hygiene and compliance in using preventing occupational diseases.